Análise e dimensionamento de torres treliçadas autoportantes para telecomunicações - Oliveira, Túlio Sales de (Universidade Federal Rural do Semi-Árido, 2018)
Self-supporting towers are structural systems composed of slender elements, which tolerate loads efficiently, with low cost and safety. However, malfunctioning or even collapse of such structures can cause damage to people's lives and / or major damage. Since the 90's, which has been making a major breakthrough in the telecommunications sector, and today, adding the possibility of data transmission, there is a significant and constant development that leads in great demand of this type of structure. This work deals with some aspects involved in the design of a telecommunications tower: characteristics of each type of tower, norms, boundary states, main actions (which structure is submitted), modeling and sizing. The modeling was performed through a static analysis using the finite element method, considering the wind incident at 0º and 45º under the structure NBR 6123/88, observing the variations of the forces in the bars, and the maximum displacements generated according to each case of wind incidence. The sizing was carried out from the efforts obtained between the two cases of wind loading, according to the requirements of NBR 8800/08.
Monografia
Keywords: Esforços; Carregamento; Análise estática; Vento; ENGENHARIAS::ENGENHARIA CIVIL